The residential habitat assessment and its influence on the land commercial value in metropolitan Arequipa from 2006 to 2016 - López Ortega, Silvia Noelia (2019)
The research consolidated in this article aims to evaluate and measure the variables of residential habitat influential in the valuation in Metropolitan Arequipa in the 2006-2016 period. The problematic that bases the investigation is placed in the Speculation generated by the non-identification of valuation factors, leaving to the subjectivity fundamental land values that are the base in the mortgage credits to have access to immovable assets. These factors are identified through a mixed method investigation, through surveys and documentation analysis, it is concluded with determination of those factors and the extent of the influence the value of the soil.